Lithium ion secondary battery, positive electrode active material, and electric device

By using high nickel content lithium nickel cobalt manganese oxide in the positive electrode sheet of lithium ion secondary battery and controlling the structure and crushing force of the secondary particles, the problem of rapid attenuation of the nickel cobalt manganese ternary material is solved, and the circulation performance of lithium ion secondary battery is improved.

CN119833714APending Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411730379.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

As the positive electrode active material, nickel-cobalt-manganese ternary material has a problem of rapid capacity decay, which affects the circulation performance of lithium-ion secondary batteries.

Method used

By using lithium nickel cobalt manganese oxide as the positive electrode active material in the positive electrode sheet of the lithium ion secondary battery, the molar content of nickel element is greater than or equal to 0.85 and less than 1. The secondary particles include radial primary particles, and the total area of ​​the radial primary particles accounts for 60% to 95% of the area of ​​the secondary particle profile, and the crushing force of the secondary particles is controlled to be 2mN to 50mN.

Benefits of technology

The circulation performance of lithium-ion secondary batteries is improved, the probability of cracking of the positive electrode active material is reduced, and the electrochemical circulation performance is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833714A_ABST
    Figure CN119833714A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to a lithium ion secondary battery, a battery and electric equipment, the lithium ion secondary battery comprises a positive electrode active material, the positive electrode active material comprises lithium nickel cobalt manganese oxide, and the molar content of a nickel element in all transition metal elements is greater than or equal to 0.85 and less than 1; the positive electrode active material comprises secondary particles, the secondary particles comprise primary particles, and the average particle size of the primary particles is 50nm-2mu m; the secondary particles comprise a first type of secondary particles, and in a profile scanning electron microscope picture of the first type of secondary particles, the total area of the radial primary particles accounts for 60%-95% of the total area of the profile of the first type of secondary particles; and the crushing force of the first type of secondary particles is 2mN-50mN. Secondary particles of the positive electrode active material are not easy to crack in the cycle process of the lithium ion secondary battery, so that the electrochemical cycle performance of the lithium ion secondary battery is relatively good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a lithium-ion secondary battery, a battery and an electrical device. Background Art

[0002] In recent years, lithium-ion batteries have made great progress. They can be widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as electric vehicles, power tools, military equipment, aerospace and other fields. Among them, when lithium-ion batteries are used in electric vehicles such as electric bicycles, electric motorcycles and electric vehicles, as the market has higher and higher requirements for the endurance of electric vehicles, the nickel-cobalt-manganese ternary material as the positive electrode active material has a phenomenon of rapid capacity decay, which needs to be further improved. Summary of the invention

[0003] In view of this, the main technical problem solved by this application is the problem of rapid capacity decay of nickel-cobalt-manganese ternary materials as positive electrode active materials, thereby providing a lithium-ion secondary battery, battery and electrical equipment that can improve the rapid decay of the cycle performance of lithium-ion secondary batteries.

[0004] The first aspect of the present application provides a lithium ion secondary battery, including a positive electrode plate, a negative electrode plate and an electrolyte, the positive electrode plate includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, the molar content of nickel in all transition metal elements is greater than or equal to 0.85 and less than 1; the positive electrode active material includes secondary particles, the secondary particles include primary particles, the average particle size of the primary particles is 50nm to 2μm; the primary particles include radial primary particles, wherein, in a cross-sectional scanning electron microscope image of the secondary particles, the long axis direction of the primary particles is the primary particles The direction of the line connecting the two farthest points on the surface; the radial direction of the secondary particle is the direction of the line connecting the nearest point of the long axis of the primary particle close to the center of the circle and the center of the circle; the radial primary particle is a primary particle whose minimum angle between the long axis direction of the primary particle and the radial direction of the secondary particle is less than or equal to 20°; the secondary particles include the first secondary particles, and in the cross-sectional scanning electron microscope image of the first secondary particles, the total area of ​​the radial primary particles accounts for 60% to 95% of the total area of ​​the cross-section of the first secondary particles; the crushing force of the first secondary particles is 2mN to 50mN.

[0005] In the embodiment of the present application, the content of nickel in lithium nickel cobalt manganese oxide is relatively high among all transition metal elements, and lithium nickel cobalt manganese oxide is a polycrystalline structure. The secondary particles of lithium nickel cobalt manganese oxide include radial primary particles, and the radial primary particles are more oriented toward the central area of ​​the spherical secondary particles. In the embodiment of the present application, by controlling the total area of ​​the radial primary particles to account for 60% to 95% of the total area of ​​the cross-section of the first secondary particles, more and larger primary particles inside the first secondary particles are oriented toward the center of the first secondary particles, the arrangement of the primary particles is more orderly, the degree of stress accumulation inside the first secondary particles is lower, and the generated stress is easier to release, reducing the probability of cracking of the first secondary particles; large-area primary particles are oriented toward the center of the first secondary particles, the radial primary particles in the first secondary particles have strong order in expansion or contraction direction, and the stress generated inside the first secondary particles is limited, reducing the probability of cracking of the first secondary particles; large-area primary particles are oriented toward the center of the first secondary particles, and the radial primary particles in the first secondary particles have strong order in expansion or contraction direction, and the stress generated inside the first secondary particles is limited, reducing the probability of cracking of the first secondary particles; large-area The accumulated primary particles are oriented toward the center of the first secondary particles, so that the local stress concentration of the first secondary particles is reduced, and the probability of local cracking of the first secondary particles can be reduced; in the embodiment of the present application, by controlling the crushing force of the first secondary particles to 2mN~50mN, the first secondary particles have a higher compressive resistance, and when the lithium-ion secondary battery is subjected to external pressure such as cold pressing during the manufacturing process, the probability of the first secondary particles being crushed is reduced; in the embodiment of the present application, by controlling the total area of ​​the radial primary particles to the total area of ​​the cross-section of the first secondary particles and the crushing force of the first secondary particles, the probability of cracking of the first secondary particles during the cold pressing manufacturing and cycling of the lithium-ion secondary battery is reduced, which can alleviate the cracking problem of the positive electrode active material and improve the cycling performance of the lithium-ion secondary battery.

[0006] In any embodiment, in the scanning electron microscope image of the cross section of the first secondary particle, the total area of ​​the radial primary particles accounts for 70% to 90% of the total area of ​​the cross section of the first secondary particle. In the embodiment of the present application, the total area of ​​the radial primary particles accounts for the total area of ​​the cross section of the first secondary particle in the above range, so that the primary particles inside the positive electrode active material are more oriented to the inside of the spherical secondary particles, the primary particles are arranged in a more orderly manner, and during the cyclic charge and discharge process, the stress accumulation degree inside the particles is low, and the generated stress is easily released, which reduces the probability of cracking of the first secondary particles, alleviates the probability of cracking of the positive electrode active material, and improves the cycle performance of the lithium-ion secondary battery.

[0007] In any embodiment, the crushing force of the first secondary particle is 10mN to 40mN. In the embodiment of the present application, the crushing force of the first secondary particle is within the above range, so that the first secondary particle has a higher compression resistance, is not prone to cracking during the production and circulation of the lithium ion secondary battery, and has better electrochemical cycle performance of the lithium ion secondary battery.

[0008] In any embodiment, the volume average particle size DV2 of the positive electrode active material is 0.5 μm to 4 μm. In the embodiment of the present application, the volume average particle size Dv2 of the positive electrode active material is within the above range, and the electrochemical performance of the positive electrode active material is better.

[0009] In any embodiment, the volume average particle size DV2 of the positive electrode active material is 0.8 μm to 3 μm. In the embodiment of the present application, the volume average particle size Dv2 of the positive electrode active material is within the above range, and the electrochemical performance of the positive electrode active material is better.

[0010] In any embodiment, the volume average particle size Dv50 of the positive electrode active material is 6 μm to 15 μm. In the embodiment of the present application, the volume average particle size Dv50 of the positive electrode active material is within the above range, the positive electrode active material has a larger specific surface area, better crushing force, and better electrochemical performance.

[0011] In any embodiment, the volume average particle size Dv50 of the positive electrode active material is 9 μm to 12 μm. In the embodiment of the present application, the volume average particle size Dv50 of the positive electrode active material is within the above range, and the electrochemical performance of the positive electrode active material is better.

[0012] In any embodiment, the average particle size of the primary particles is 100 nm to 500 nm. In the embodiment of the present application, the average particle size of the primary particles is within the above range, so that the stress accumulation degree inside the secondary particles is lower and the generated stress is easier to release.

[0013] In any embodiment, in the cross-sectional scanning electron microscope image of the secondary particles, the major axis length of the primary particles is 0.3 μm to 3 μm. In the embodiment of the present application, the major axis length of the primary particles is within the above range, and the secondary particles are easy to release stress, so that the stress accumulation degree of the secondary particles is reduced and the structural stability of the secondary particles is increased.

[0014] In any embodiment, in the cross-sectional scanning electron microscope image of the secondary particle, the major axis length of the primary particle is 0.5 μm to 2 μm. In the embodiment of the present application, the major axis length of the primary particle is within the above range, so that the stress accumulation degree of the secondary particle is low and the structural stability of the secondary particle is good.

[0015] In any embodiment, the cross-sectional porosity of the positive electrode active material is 2% to 8%. In the embodiment of the present application, the cross-sectional porosity of the positive electrode active material is within the above range, so that the positive electrode active material can release stress, alleviate the occurrence of secondary particle cracking of the positive electrode active material, improve the compressive strength of the positive electrode active material, and improve the electrochemical cycle performance of the lithium ion secondary battery.

[0016] In any embodiment, the cross-sectional porosity of the positive electrode active material is 3% to 6%. In the embodiment of the present application, the cross-sectional porosity of the positive electrode active material is within the above range, so that the positive electrode active material can release stress, alleviate the occurrence of secondary particle cracking of the positive electrode active material, improve the compressive strength of the positive electrode active material, and improve the electrochemical cycle performance of the lithium ion secondary battery.

[0017] In any embodiment, the cross-sectional average pore size of the positive electrode active material ranges from 0.1 μm to 2 μm. In the embodiment of the present application, the cross-sectional average pore size of the positive electrode active material is within the above range, so that the positive electrode active material can well relieve stress and release stress, and the compaction density of the positive electrode active material is better, so that the capacity density of the lithium ion secondary battery is better.

[0018] In any embodiment, the positive electrode active material is 0 to 4.9×10 4 N, the volume average particle size Dv2 of the positive electrode active material changes by less than or equal to 20%. In the embodiment of the present application, within the range of 0 to 4.9×10 4 Within the pressure range of N, the change rate of the volume average particle size Dv2 of the positive active material is small, indicating that the amount of micropowder particles (volume average particle size Dv2) is at a low level, indicating that the crushing force of the positive active material is large.

[0019] In some embodiments, the amount of the first type of secondary particles in the secondary particles accounts for 80% to 100%. In the embodiments of the present application, the amount of the first type of secondary particles in the secondary particles accounts for a large amount, and the first type of secondary particles has a major influence on the performance of the positive electrode active material. The first type of secondary particles can alleviate the problem of secondary particle cracking. The first type of secondary particles has better performance, which can effectively improve the overall performance of the positive electrode active material, reduce the probability of secondary particle cracking of the positive electrode active material during the cycle, and improve the cycle stability of the lithium-ion secondary battery.

[0020] In some embodiments, the amount of the first type of secondary particles in the secondary particles accounts for 90% to 100%. In the embodiment of the present application, the amount of the first type of secondary particles in the secondary particles accounts for a larger amount, which can effectively improve the overall performance of the positive electrode active material, reduce the probability of secondary particles cracking in the positive electrode active material during the cycle, and improve the cycle stability of the lithium ion secondary battery.

[0021] In any embodiment, the nickel content of the first secondary particle from the center to the surface area is equal, or the difference in the nickel content from the center to the surface area is less than or equal to 2%. The manganese content of the first secondary particle from the center to the surface area is equal, or the difference in the manganese content from the center to the surface area is less than or equal to 0.5%. In the embodiment of the present application, the nickel and manganese content in the first secondary particle is uniform from the center area to the surface area, that is, the nickel and manganese elements in the first secondary particle are uniformly distributed, which will reduce the defects of the positive electrode active material, reduce the uneven distribution of element concentration in local areas, and promote Li + Embedding and de-embedding are beneficial to the capacity of the positive electrode active material; the nickel and manganese elements are evenly distributed in the first secondary particles, which alleviates the unevenness of Li+ embedding and de-embedding, reduces local differences, and improves the cycle stability of lithium-ion secondary batteries.

[0022] In any embodiment, the positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 e O f The material, wherein the M1 element is one or more combinations of Zr, Ti, Y, Sb, W, Mo, Ba, Ta, Nb, Al, etc., 0.9≤a≤1.2, 0.85≤b<1, 0.01≤c≤0.09, 0.01≤d≤0.05, 0.001≤e≤0.005, 1.8≤f≤2.2, b+c+d+e=1. In the embodiment of the present application, the positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 e O f The material, lithium nickel cobalt manganese oxide can be doped with metal element M1, which can improve the electrochemical properties of lithium nickel cobalt manganese oxide.

[0023] In any embodiment, 0.9≤b<1, and / or, 0.002≤e≤0.004. In the embodiment of the present application, in the lithium nickel cobalt manganese oxide, the molar content of nickel in all transition metal elements is greater than or equal to 0.9. Or the doping element is within the above range, which can improve the electrochemical performance of the lithium nickel cobalt manganese oxide.

[0024] In any embodiment, the structural formula is Li a Ni b Co c Mn d M1 e O fThe surface of the material further includes a coating layer, and the coating layer includes Co and / or B elements. In the embodiment of the present application, by a Ni b Co c Mn d M1 e O f The surface of the material is coated with a substance containing the Co element, which can penetrate into the grain boundaries of the primary particles, repair the grain boundaries, and improve the Young's modulus of the secondary particles. The coating layer contains the B element, which can refine the primary grains, improve the ability of lithium ions to be deintercalated on the surface, and improve the electrochemical performance of lithium-ion secondary batteries.

[0025] The second aspect of the present application also provides a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, the molar content of nickel in all transition metal elements is greater than or equal to 0.85 and less than 1; the positive electrode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 50nm~2μm; the primary particles include radial primary particles, wherein, in the cross-sectional scanning electron microscope image of the secondary particles, the long axis direction of the primary particles is the direction of the line connecting the two farthest points on the surface of the primary particles, the radial direction of the secondary particles is the direction of the line connecting the nearest point of the long axis of the primary particles close to the center of the circle and the center of the circle, and the radial primary particles are primary particles whose minimum angle between the long axis direction of the primary particles and the radial direction of the secondary particles is less than or equal to 20°; the secondary particles include the first secondary particles, and in the cross-sectional scanning electron microscope image of the first secondary particles, the total area of ​​the radial primary particles accounts for 60%~95% of the total area of ​​the cross-section of the first secondary particles; the crushing force of the first secondary particles is 2mN~50mN.

[0026] In the embodiment of the present application, the content of nickel in lithium nickel cobalt manganese oxide is relatively high among all transition metal elements, and lithium nickel cobalt manganese oxide is a polycrystalline structure. The secondary particles of lithium nickel cobalt manganese oxide include radial primary particles, and the radial primary particles are more oriented toward the central area of ​​the spherical secondary particles. In the embodiment of the present application, by controlling the total area of ​​the radial primary particles to account for 60% to 95% of the total area of ​​the cross-section of the first secondary particles, more and larger primary particles inside the first secondary particles are oriented toward the center of the first secondary particles, and the arrangement of the primary particles is more orderly. During the cyclic charge and discharge process, the stress accumulation inside the first secondary particles is lower, and the generated stress is easier to release, reducing the probability of cracking of the first secondary particles; the large-area primary particles are oriented toward the center of the first secondary particles, and the radial primary particles in the first secondary particles have strong order in expansion or contraction direction, and the stress generated inside the first secondary particles is limited, reducing the probability of cracking of the first secondary particles. probability; a large area of ​​primary particles is oriented toward the center of the first secondary particles, so that the local stress concentration of the first secondary particles is reduced, and the probability of local cracking of the first secondary particles can be reduced; in the embodiment of the present application, by controlling the crushing force of the first secondary particles to be 2mN~50mN, the first secondary particles have a higher compressive resistance, and when the lithium-ion secondary battery is subjected to external pressure such as cold pressing during the manufacturing process, the probability of the first secondary particles being crushed is reduced; in the embodiment of the present application, by controlling the total area of ​​the radial primary particles to the total area of ​​the cross-section of the first secondary particles and the crushing force of the first secondary particles, the probability of cracking of the first secondary particles during the cold pressing manufacturing and cycling of the lithium-ion secondary battery is reduced, which can alleviate the cracking problem of the positive electrode active material and improve the cycling performance of the lithium-ion secondary battery.

[0027] The third aspect of the present application also provides an electrical device, comprising the lithium ion secondary battery of the first aspect and / or the positive electrode active material of the second aspect, which has the advantages that the lithium ion secondary battery of the first aspect and / or the positive electrode active material of the second aspect are the same or similar.

[0028] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic structural diagram of a lithium-ion secondary battery according to one embodiment of the present application.

[0030] Figure 2 It is a schematic diagram of the exploded structure of a battery according to one embodiment of the present application.

[0031] Figure 3 It is a schematic diagram of the partial structure of an electrical equipment according to one embodiment of the present application.

[0032] Figure 4 This is a scanning electron microscope image of the first type of lithium nickel cobalt manganese oxide in Example 1 of the present application. DETAILED DESCRIPTION

[0033] Hereinafter, the embodiments of the lithium-ion secondary battery, battery and electrical equipment of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0034] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0035] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0036] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0037] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0038] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.

[0039] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0040] For lithium nickel cobalt manganese oxide with a high nickel content, especially lithium nickel cobalt manganese oxide in which the molar content of nickel in all transition metal elements is greater than or equal to 0.85, and polycrystalline lithium nickel cobalt manganese oxide, which is used as a positive electrode active material, the particles of the lithium nickel cobalt manganese oxide will crack during the charge and discharge process, the electrochemical performance of the lithium-ion secondary battery will decrease rapidly, and the life of the lithium-ion secondary battery will be reduced.

[0041] Based on this, the present application proposes that the first aspect of the present application provides a lithium-ion secondary battery, which, in any embodiment, includes a positive electrode sheet, a negative electrode sheet and an electrolyte, the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel in all transition metal elements is greater than or equal to 0.85 and less than 1; the positive electrode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 50nm to 2μm; the primary particles include radial primary particles, wherein, in a cross-sectional scanning electron microscope image of the secondary particles, the length of the primary particles is The axial direction is the direction of the line connecting the two farthest points on the surface of the primary particle, the radial direction of the secondary particle is the direction of the line connecting the nearest point of the long axis of the primary particle close to the center of the circle and the center of the circle, and the radial primary particle is a primary particle whose minimum angle between the long axis direction of the primary particle and the radial direction of the secondary particle is less than or equal to 20°; the secondary particles include the first secondary particles, and in the cross-sectional scanning electron microscope image of the first secondary particles, the total area of ​​the radial primary particles accounts for 60% to 95% of the total area of ​​the cross-section of the first secondary particles, and the crushing force of the first secondary particles is 2mN to 50mN.

[0042] In the embodiment of the present application, the content of nickel in lithium nickel cobalt manganese oxide is relatively high among all transition metal elements, and lithium nickel cobalt manganese oxide is a polycrystalline structure. The secondary particles of lithium nickel cobalt manganese oxide include radial primary particles, and the radial primary particles are more oriented toward the central area of ​​the spherical secondary particles. In the embodiment of the present application, by controlling the total area of ​​the radial primary particles to account for 60% to 95% of the total area of ​​the cross-section of the first secondary particles, more and larger primary particles inside the first secondary particles are oriented toward the center of the first secondary particles, and the arrangement of the primary particles is more orderly. During the cyclic charge and discharge process, the stress accumulation inside the first secondary particles is lower, and the generated stress is easier to release, reducing the probability of cracking of the first secondary particles; the large-area primary particles are oriented toward the center of the first secondary particles, and the radial primary particles in the first secondary particles have strong order in expansion or contraction direction, and the stress generated inside the first secondary particles is limited, reducing the probability of cracking of the first secondary particles. probability; a large area of ​​primary particles is oriented toward the center of the first secondary particles, so that the local stress concentration of the first secondary particles is reduced, and the probability of local cracking of the first secondary particles can be reduced; in the embodiment of the present application, by controlling the crushing force of the first secondary particles to be 2mN~50mN, the first secondary particles have a higher compressive resistance, and when the lithium-ion secondary battery is subjected to external pressure such as cold pressing during the manufacturing process, the probability of the first secondary particles being crushed is reduced; in the embodiment of the present application, by controlling the total area of ​​the radial primary particles to the total area of ​​the cross-section of the first secondary particles and the crushing force of the first secondary particles, the probability of cracking of the first secondary particles during the cold pressing manufacturing and cycling of the lithium-ion secondary battery is reduced, which can alleviate the cracking problem of the positive electrode active material and improve the cycling performance of the lithium-ion secondary battery.

[0043] The molar content of nickel in all transition metal elements can be 0.85, 0.88, 0.9, 0.93, 0.95, 0.96, 0.98, etc., or a range value consisting of any two of the above values, for example, 0.85-0.9, 0.9-0.96, 0.96-0.98, or 0.98 or more. The average particle size of the primary particles can be 50nm, 80nm, 100nm, 500nm, 800nm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, etc., or a range value consisting of any two of the above values, for example, 50nm-800nm, 800nm-1.2μm, 1.2μm-2μm, etc. In the scanning electron microscope image of the cross section of the first secondary particle, the total area of ​​the radial primary particles accounts for 60%, 68%, 70%, 74%, 80%, 83%, 90%, 95%, etc. of the total area of ​​the cross section of the first secondary particle, or a range value consisting of any two of the above values, for example, 60% to 68%, 68% to 83%, 83% to 95%, etc. The crushing force of the first secondary particle can be 2mN, 5mN, 10mN, 16mN, 20mN, 27mN, 30mN, 50mN, etc., or a range value consisting of any two of the above values, for example, 2mN to 16mN, 16mN to 27mN, 27mN to 50mN, etc.

[0044] The crushing force of the first secondary particles is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.

[0045] The average particle size of the primary particles is common knowledge in the art, has a meaning commonly known in the art, and can be measured by methods and instruments in the art.

[0046] The total area of ​​the cross section of the first secondary particle is the area enclosed by the edge region in the cross section scanning electron microscope image of a single first secondary particle. The total area of ​​the radial primary particles is the sum of the areas of all radial primary particles in the cross section scanning electron microscope image of a single first secondary particle. The area of ​​the radial primary particles is the area enclosed by the edge or boundary of the radial primary particles.

[0047] Wherein, all the secondary particles are the first secondary particles, or the secondary particles include the first secondary particles and the second secondary particles. The total area of ​​the radial primary particles of the second secondary particles accounts for less than 60% of the total area of ​​the cross section of the first secondary particles. In the embodiment of the present application, the first secondary particles are the main component of the secondary particles and play a major role in the influence on the positive electrode active material.

[0048] In any embodiment, in the cross-sectional scanning electron microscope image of the first secondary particle, the total area of ​​the radial primary particles accounts for 70% to 90% of the total area of ​​the cross-sectional area of ​​the first secondary particle. In the embodiment of the present application, the total area of ​​the radial primary particles accounts for the total area of ​​the cross-sectional area of ​​the first secondary particle in the above range, so that the primary particles inside the positive electrode active material are more oriented to the inside of the spherical secondary particles, and the primary particles are arranged in a high degree of order. During the cyclic charge and discharge process, the stress accumulation degree inside the particles is low, and the generated stress is easily released, thereby improving the particle strength of the material and alleviating the problem of particle cracking. In the cross-sectional scanning electron microscope image of the first secondary particle, the total area of ​​the radial primary particles accounts for 70%, 74%, 80%, 83%, 90%, etc., or a range value composed of any two of the above values, for example, 70% to 74%, 74% to 83%, 83% to 90%, etc.

[0049] In any embodiment, the crushing force of the first secondary particle is 10mN to 40mN. In the embodiment of the present application, the crushing force of the first secondary particle is within the above range, so that the first secondary particle has a higher compressive resistance, and is not prone to cracking during the production and circulation of lithium-ion secondary batteries, so that the electrochemical cycle performance of lithium-ion secondary batteries is better. The crushing force of the first secondary particle can be 10mN, 16mN, 20mN, 27mN, 30mN, 40mN, etc., or a range value composed of any two of the above values, for example, 10mN to 16mN, 16mN to 27mN, 27mN to 40mN, etc.

[0050] In any embodiment, the volume average particle size DV2 of the positive electrode active material is 0.5μm to 4μm. In the embodiment of the present application, the volume average particle size Dv2 of the positive electrode active material is within the above range, and the electrochemical performance of the positive electrode active material is better. Among them, the volume average particle size Dv2 of the positive electrode active material can be 0.5μm, 0.8μm, 1μm, 2μm, 3μm, 4μm, etc., or a range value composed of any two of the above values, for example, 0.5μm to 0.8μm, 0.8μm to 1μm, 1μm to 2μm, 2μm to 3μm, 3μm to 4μm, etc.

[0051] The volume average particle size Dv2 is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.

[0052] In any embodiment, the volume average particle size DV2 of the positive electrode active material is 0.8 μm to 3 μm. In the embodiment of the present application, the volume average particle size Dv2 of the positive electrode active material is within the above range, and the electrochemical performance of the positive electrode active material is better. Among them, the volume average particle size Dv2 of the positive electrode active material can be 0.8 μm, 1 μm, 2 μm, 3 μm, etc., or a range value composed of any two of the above values, for example, 0.8 μm to 1 μm, 1 μm to 2 μm, 2 μm to 3 μm, etc.

[0053] In some embodiments, the volume average particle size Dv50 of the positive electrode active material is 6μm to 15μm. In the embodiment of the present application, the volume average particle size Dv50 of the positive electrode active material is in the above range, the positive electrode active material has a larger specific surface area, better crushing force, and better electrochemical performance of the positive electrode active material. Among them, the volume average particle size Dv50 of the positive electrode active material can be 6μm, 9μm, 10μm, 13μm, 15μm, etc., or a range value composed of any two of the above values, for example, 6μm to 10μm, 10μm to 13μm, 13μm to 15μm, etc.

[0054] The volume average particle size Dv50 is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.

[0055] In some embodiments, the volume average particle size Dv50 of the positive electrode active material is 9 μm to 12 μm. In the embodiment of the present application, the volume average particle size Dv50 of the positive electrode active material is within the above range, and the electrochemical performance of the positive electrode active material is better. Among them, the volume average particle size Dv50 of the positive electrode active material can be 9 μm, 10 μm, 11 μm, 12 μm, etc., or a range value composed of any two of the above values, for example, 9 μm to 10 μm, 10 μm to 11 μm, 11 μm to 12 μm, etc.

[0056] In some embodiments, the average particle size of the primary particles is 100nm to 500nm. In the embodiment of the present application, the average particle size of the primary particles is within the above range, so that the stress accumulation degree inside the secondary particles is lower and the generated stress is more easily released. The average particle size of the primary particles can be 50nm, 80nm, 100nm, 300nm, 500nm, etc., or a range value composed of any two of the above values, for example, 50nm to 80nm, 80nm to 300nm, 300nm to 500nm, etc.

[0057] In some embodiments, in the cross-sectional scanning electron microscope image of the secondary particles, the major axis length of the primary particles is 0.3 μm to 3 μm. In the embodiment of the present application, the major axis length of the primary particles is within the above range, and the secondary particles are easy to release stress, so that the stress accumulation degree of the secondary particles is reduced, the structural stability of the secondary particles is increased, and the compressive strength of the secondary particles is increased. Among them, the major axis length of the primary particles can be 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.3 μm, 2 μm, 2.2 μm, 2.6 μm, 3 μm, etc., or a range value composed of any two of the above values, for example, 0.3 μm to 1 μm, 1 μm to 2.2 μm, 2.2 μm to 3 μm, etc.

[0058] In some embodiments, in the cross-sectional scanning electron microscope image of the secondary particles, the major axis length of the primary particles is 0.5 μm to 2 μm. In the embodiment of the present application, the major axis length of the primary particles is within the above range, so that the stress accumulation degree of the secondary particles is low, the structural stability of the secondary particles is good, and the compressive strength of the secondary particles is good. Among them, the major axis length of the primary particles can be 0.5 μm, 0.8 μm, 1 μm, 1.3 μm, 2 μm, etc., or a range value composed of any two of the above values, for example, 0.5 μm to 0.8 μm, 0.8 μm to 1.3 μm, 1.3 μm to 2 μm, etc.

[0059] In some embodiments, the cross-sectional porosity of the positive electrode active material is 2% to 8%. In the embodiment of the present application, the cross-sectional porosity of the positive electrode active material is within the above range, so that the positive electrode active material can release stress, alleviate the occurrence of secondary particle cracking of the positive electrode active material, improve the compressive strength of the positive electrode active material, and improve the electrochemical cycle performance of the lithium-ion secondary battery. Among them, the cross-sectional porosity of the positive electrode active material can be 2%, 4%, 5%, 6%, 8%, etc., or a range value composed of any two of the above values, for example, 2% to 4%, 4% to 6%, 6% to 8%, etc.

[0060] The cross-sectional porosity is common knowledge in the art, has a meaning commonly known in the art, and can be measured by methods and instruments in the art.

[0061] In some embodiments, the cross-sectional porosity of the positive electrode active material is 3% to 6%. In the embodiment of the present application, the cross-sectional porosity of the positive electrode active material is within the above range, so that the positive electrode active material can release stress, alleviate the occurrence of secondary particle cracking of the positive electrode active material, improve the compressive strength of the positive electrode active material, and improve the electrochemical cycle performance of the lithium-ion secondary battery. Among them, the cross-sectional porosity of the positive electrode active material can be 3%, 4%, 5%, 6%, etc., or a range value composed of any two of the above values, for example, 3% to 4%, 4% to 5%, 5% to 6%, etc.

[0062] In some embodiments, the cross-sectional average pore size of the positive electrode active material is 0.1 μm to 2 μm. In the embodiment of the present application, the cross-sectional average pore size of the positive electrode active material is within the above range, so that the positive electrode active material can well relieve stress and release stress, and the compaction density of the positive electrode active material is better, so that the capacity density of the lithium-ion secondary battery is better. Among them, the cross-sectional average pore size of the positive electrode active material can be 0.1 μm, 0.8 μm, 1 μm, 1.3 μm, 2 μm, etc., or a range value composed of any two of the above values, for example, 0.1 μm to 0.8 μm, 0.8 μm to 1.3 μm, 1.3 μm to 2 μm, etc.

[0063] The cross-sectional average pore size is common knowledge in the art, has a meaning commonly known in the art, and can be measured by methods and instruments in the art.

[0064] In any embodiment, the positive electrode active material is 0 to 4.9×10 4 N, the volume average particle size Dv2 of the positive electrode active material changes by less than or equal to 20%. In the embodiment of the present application, within the range of 0 to 4.9×10 4 N pressure range, the change rate of the volume average particle size Dv2 of the positive active material is small, indicating that the amount of micropowder particles (volume average particle size Dv2) is at a low level, indicating that the crushing force of the positive active material is large. 4 Within the pressure range of N, the change rate of the volume average particle size Dv2 of the positive electrode active material can be 0, 1%, 5%, 7%, 10%, 15%, 18%, 20%, etc., or a range value composed of any two of the above values, for example, 0~5%, 5%~18% μm, 18%~20%, etc.

[0065] In some embodiments, the number of the first secondary particles in the secondary particles accounts for 80% to 100%. In the embodiment of the present application, the number of the first secondary particles in the secondary particles accounts for a large proportion, and the first secondary particles have a major influence on the performance of the positive electrode active material. The first secondary particles can alleviate the problem of secondary particle cracking. The first secondary particles have better performance, which can effectively improve the overall performance of the positive electrode active material, reduce the probability of secondary particle cracking of the positive electrode active material during the cycle, and improve the cycle stability of the lithium-ion secondary battery. Among them, the number of the first secondary particles in the secondary particles accounts for 80%, 84%, 90%, 96%, 100%, etc., or a range value composed of any two of the above values, for example, 80% to 84%, 84% to 90%, 90% to 100%, etc. The number of the second secondary particles in the secondary particles accounts for less than 20%, which has little effect on the positive electrode active material.

[0066] In some embodiments, the number of the first type of secondary particles in the secondary particles accounts for 90% to 100%. In the embodiment of the present application, the number of the first type of secondary particles in the secondary particles accounts for a larger proportion, which can effectively improve the overall performance of the positive electrode active material, reduce the probability of secondary particles cracking in the positive electrode active material during the cycle, and improve the cycle stability of the lithium-ion secondary battery. Among them, the number of the first type of secondary particles in the secondary particles accounts for 90%, 94%, 95%, 98%, 100%, etc., or a range value composed of any two of the above values, for example, 90% to 94%, 94% to 98%, 98% to 100%, etc.

[0067] In some embodiments, the nickel content of the first secondary particle from the center to the surface area is equal, or the difference in the nickel content from the center to the surface area is less than or equal to 2%. The manganese content of the first secondary particle from the center to the surface area is equal, or the difference in the manganese content from the center to the surface area is less than or equal to 0.5%. In the embodiment of the present application, the nickel and manganese content in the first secondary particle is uniform from the center area to the surface area, that is, the nickel and manganese elements in the first secondary particle are uniformly distributed, which will reduce the defects of the positive electrode active material, reduce the uneven distribution of element concentrations in local areas, and promote Li + Embedding and de-embedding are beneficial to the capacity of the positive electrode active material; the nickel and manganese elements are evenly distributed in the first secondary particles, which alleviates the unevenness of Li+ embedding and de-embedding, reduces local differences, and improves the cycle stability of lithium-ion secondary batteries.

[0068] In the embodiment of the present application, the content of nickel refers to the mass ratio of nickel to all elements in the test area. The content of manganese refers to the mass ratio of manganese to all elements in the test area.

[0069] In some embodiments, when the coating layer on the surface of the positive electrode active material does not have cobalt, the content of cobalt in the first secondary particle from the center to the surface area is equal, or the difference in the content of cobalt from the center to the surface area is less than or equal to 0.6%. In the embodiment of the present application, the content of cobalt in the first secondary particle is uniform from the center area to the surface area, that is, the cobalt in the first secondary particle is uniformly distributed.

[0070] In some embodiments, the positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 e O fThe material, wherein the M1 element is one or more combinations of Zr, Ti, Y, Sb, W, Mo, Ba, Ta, Nb, Al, etc., 0.9≤a≤1.2, 0.85≤b<1, 0.01≤c≤0.09, 0.01≤d≤0.05, 0.001≤e≤0.005, 1.6≤f≤2.4, b+c+d+e=1. In the embodiment of the present application, the positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 e O f The material, lithium nickel cobalt manganese oxide can be doped with metal element M1, which can improve the electrochemical properties of lithium nickel cobalt manganese oxide.

[0071] In some embodiments, 0.9≤b<1, and / or, 0.002≤e≤0.004. In the embodiment of the present application, in the lithium nickel cobalt manganese oxide, the molar content of nickel in all transition metal elements is greater than or equal to 0.9. Or the doping element is within the above range, which can improve the electrochemical performance of the lithium nickel cobalt manganese oxide.

[0072] In some embodiments, the structural formula is Li a Ni b Co c Mn d M1 e O f The surface of the material further includes a coating layer, and the coating layer includes Co and / or B elements. In the embodiment of the present application, by a Ni b Co c Mn d M1 e O f The surface of the material is coated with a substance containing the Co element, which can penetrate into the grain boundaries of the primary particles, repair the grain boundaries, and improve the Young's modulus of the secondary particles. The coating layer contains the B element, which can refine the primary grains, improve the ability of lithium ions to be deintercalated on the surface, and improve the electrochemical performance of lithium-ion secondary batteries.

[0073] The second aspect of the present application also provides a positive electrode active material, the positive electrode active material includes the positive electrode active material in the lithium ion secondary battery of the first aspect, specifically, the positive electrode active material includes lithium nickel cobalt manganese oxide, the molar content of nickel element in all transition metal elements is greater than or equal to 0.85 and less than 1; the positive electrode active material includes secondary particles, the secondary particles include primary particles, the average particle size of the primary particles is 50nm to 2μm; the primary particles include radial primary particles, wherein, in the cross-sectional scanning electron microscope image of the secondary particles, the long axis direction of the primary particles is the primary particles. The radial direction of the secondary particle is the direction of the line connecting the two farthest points on the particle surface, the radial direction of the secondary particle is the direction of the line connecting the nearest point of the long axis of the primary particle close to the center of the circle and the center of the circle, and the radial primary particle is a primary particle whose minimum angle between the long axis direction of the primary particle and the radial direction of the secondary particle is less than or equal to 20°; the secondary particles include the first secondary particles, and in the cross-sectional scanning electron microscope image of the first secondary particles, the total area of ​​the radial primary particles accounts for 60% to 95% of the total area of ​​the cross-section of the first secondary particles, and the crushing force of the first secondary particles is 2mN to 50mN.

[0074] In the embodiment of the present application, the content of nickel in lithium nickel cobalt manganese oxide is relatively high among all transition metal elements, and lithium nickel cobalt manganese oxide is a polycrystalline structure. The secondary particles of lithium nickel cobalt manganese oxide include radial primary particles, and the radial primary particles are more oriented toward the central area of ​​the spherical secondary particles. In the embodiment of the present application, by controlling the total area of ​​the radial primary particles to account for 60% to 95% of the total area of ​​the cross-section of the first secondary particles, more and larger primary particles inside the first secondary particles are oriented toward the center of the first secondary particles, and the arrangement of the primary particles is more orderly. During the cyclic charge and discharge process, the stress accumulation inside the first secondary particles is lower, and the generated stress is easier to release, reducing the probability of cracking of the first secondary particles; the large-area primary particles are oriented toward the center of the first secondary particles, and the radial primary particles in the first secondary particles have strong order in expansion or contraction direction, and the stress generated inside the first secondary particles is limited, reducing the probability of cracking of the first secondary particles. probability; a large area of ​​primary particles is oriented toward the center of the first secondary particles, so that the local stress concentration of the first secondary particles is reduced, and the probability of local cracking of the first secondary particles can be reduced; in the embodiment of the present application, by controlling the crushing force of the first secondary particles to be 2mN~50mN, the first secondary particles have a higher compressive resistance, and when the lithium-ion secondary battery is subjected to external pressure such as cold pressing during the manufacturing process, the probability of the first secondary particles being crushed is reduced; in the embodiment of the present application, by controlling the total area of ​​the radial primary particles to the total area of ​​the cross-section of the first secondary particles and the crushing force of the first secondary particles, the probability of cracking of the first secondary particles during the cold pressing manufacturing and cycling of the lithium-ion secondary battery is reduced, which can alleviate the cracking problem of the positive electrode active material and improve the cycling performance of the lithium-ion secondary battery.

[0075] The molar content of nickel in all transition metal elements can be 0.85, 0.88, 0.9, 0.93, 0.95, 0.96, 0.98, etc., or a range value consisting of any two of the above values, for example, 0.85-0.9, 0.9-0.96, 0.96-0.98, or 0.98 or more. The average particle size of the primary particles can be 50nm, 80nm, 100nm, 500nm, 800nm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, etc., or a range value consisting of any two of the above values, for example, 50nm-800nm, 800nm-1.2μm, 1.2μm-2μm, etc. In the scanning electron microscope image of the cross section of the first secondary particle, the total area of ​​the radial primary particles accounts for 60%, 68%, 70%, 74%, 80%, 83%, 90%, 95%, etc. of the total area of ​​the cross section of the first secondary particle, or a range value consisting of any two of the above values, for example, 60% to 68%, 68% to 83%, 83% to 95%, etc. The crushing force of the first secondary particle can be 2mN, 5mN, 10mN, 16mN, 20mN, 27mN, 30mN, 50mN, etc., or a range value consisting of any two of the above values, for example, 2mN to 16mN, 16mN to 27mN, 27mN to 50mN, etc.

[0076] The third aspect of the present application also provides an electrical device, comprising the lithium ion secondary battery and / or the positive electrode active material of the second aspect, which has the advantages that the lithium ion secondary battery of the first aspect and / or the positive electrode active material of the second aspect are the same or similar.

[0077] In addition, the lithium ion secondary battery, battery cell, and electric equipment of the present application will be described below with reference to the drawings as appropriate.

[0078] In the embodiments of the present application, a battery cell refers to the smallest unit that makes up a battery. A battery cell also includes an electrolyte and a separator. The separator is disposed between the positive electrode and the negative electrode, and mainly serves to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. During the battery charging and discharging process, the active ions Li + The electrolyte is embedded and released back and forth between the positive electrode and the negative electrode, and plays the role of conducting ions between the positive electrode and the negative electrode.

[0079] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the above embodiment of the present application.

[0080] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0081] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0082] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0083] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0084] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0085] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes the negative electrode active material of the above embodiment.

[0086] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0087] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0088] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0089] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0090] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)).

[0091] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0092] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.

[0093] In some embodiments, the electrolyte includes an electrolyte salt and a solvent.

[0094] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0095] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0096] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0097] In some embodiments, the lithium-ion secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0098] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0099] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be made into a battery cell assembly by a winding process or a lamination process.

[0100] In some embodiments, Figure 1 As shown, the battery cell may include an outer package. The outer package may be used to encapsulate the battery cell assembly 11 and the electrolyte. The outer package includes an end cap 12, a housing 13 and other functional components.

[0101] The end cap 12 refers to a component that covers the opening of the shell 13 to isolate the internal environment of the battery cell 10 from the external environment. Without limitation, the shape of the end cap 12 can be adapted to the shape of the shell 13 to match the shell 13. Optionally, the end cap 12 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 12 is not easily deformed when squeezed and collided, so that the battery cell 10 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 12a can be provided on the end cap 12. The electrode terminal 12a can be used to electrically connect to the battery cell assembly 11 for outputting or inputting electrical energy of the battery cell 10. In some embodiments, the end cap 12 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 10 reaches a threshold. The material of the end cap 12 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose special restrictions on this. In some embodiments, an insulating member (not shown) may be provided inside the end cap 12 to isolate the electrical connection components in the housing 13 from the end cap 12 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.

[0102] The shell 13 is a component used to cooperate with the end cap 12 to form the internal environment of the battery cell 10, wherein the formed internal environment can be used to accommodate the battery cell assembly 11, electrolyte and other components. The shell 13 and the end cap 12 can be independent components, and an opening can be set on the shell 13, and the internal environment of the battery cell 10 is formed by covering the opening with the end cap 12 at the opening. Without limitation, the end cap 12 and the shell 13 can also be integrated. Specifically, the end cap 12 and the shell 13 can form a common connection surface before other components are put into the shell, and when the interior of the shell 13 needs to be encapsulated, the end cap 12 covers the shell 13. The shell 13 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 13 can be determined according to the specific shape and size of the battery cell assembly 11. The material of the shell 13 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.

[0103] The housing 13 may contain one or more battery cell assemblies 11. The portions of the positive and negative electrodes that do not contain active materials each constitute a tab 11a. The positive tab and the negative tab may be located at one end of the main body or at both ends of the main body. During the charge and discharge process of the battery, the positive active material and the negative active material react with the electrolyte, and the tab 11a connects the electrode terminal to form a current loop.

[0104] Please refer to Figure 2 , Figure 2 A schematic diagram of the exploded structure of a battery cell 100 provided in some embodiments of the present application. The battery cell 100 includes a box 20 and a battery cell 10, and the battery cell 10 is contained in the box 20. Among them, the box 20 is used to provide a storage space for the battery cell 10, and the box 20 can adopt a variety of structures. In some embodiments, the box 20 may include a first part 21 and a second part 22, the first part 21 and the second part 22 cover each other, and the first part 21 and the second part 22 jointly define a storage space for accommodating the battery cell 10. The second part 22 may be a hollow structure with one end open, the first part 21 may be a plate-like structure, and the first part 21 covers the open side of the second part 22, so that the first part 21 and the second part 22 jointly define a storage space; the first part 21 and the second part 22 may also be hollow structures with one side open, and the open side of the first part 21 covers the open side of the second part 22. Of course, the box 20 formed by the first part 21 and the second part 22 may be in a variety of shapes, such as a cylinder, a cuboid, etc.

[0105] In the lithium-ion secondary battery 100, there may be multiple battery cells 10, and the multiple battery cells 10 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 10 are both connected in series and in parallel. The multiple battery cells 10 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 10 is accommodated in the box 20; of course, the lithium-ion secondary battery 100 may also be a battery module formed by connecting multiple battery cells 10 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 20. The lithium-ion secondary battery 100 may also include other structures, for example, the lithium-ion secondary battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 10.

[0106] The battery cell 10 may be cylindrical, flat, rectangular or in other shapes.

[0107] In some embodiments, the lithium-ion secondary battery 100 can be assembled into a battery module. The number of batteries contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0108] In addition, the present application also provides an electrical device, which includes at least one of the lithium-ion secondary batteries and / or battery cells provided in the present application. The lithium-ion secondary battery or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0109] As the electrical equipment, a lithium-ion secondary battery and / or a battery can be selected according to its usage requirements.

[0110] Figure 3 As shown, it is an electric device as an example. The electric device is a vehicle such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. A structural schematic diagram of a vehicle 1000 is specifically provided. A lithium-ion secondary battery 100 is arranged inside the vehicle 1000, and the lithium-ion secondary battery 100 can be arranged at the bottom, head or tail of the vehicle 1000. The lithium-ion secondary battery 100 can be used to power the vehicle 1000, for example, the lithium-ion secondary battery 100 can be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the lithium-ion secondary battery 100 to power the motor 300, for example, for the working power demand of the vehicle 1000 during starting, navigation and driving.

[0111] In some embodiments of the present application, the lithium-ion secondary battery 100 can be used not only as an operating power source for the vehicle 1000, but also as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.

[0112] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0113] Example 1

[0114] Preparation method of positive electrode active material:

[0115] S1: Preparation of nickel-cobalt-manganese hydroxide drive body by coprecipitation reaction: According to the molar ratio of Ni, Co and Mn elements in the high-nickel ternary material substrate of 0.917:0.07:0.01, a sulfate solution of Ni, Co and Mn with a concentration of 6 mol / L is prepared, and a 12 mol / L NaOH solution (precipitant) and a 20 mol / L ammonia solution (complexing agent) are prepared at the same time. Pure water with a volume ratio of 30% is added to the reactor, and the above three solutions are pumped into the reactor. The flow rate of sulfate and ammonia water is kept constant during the reaction. The stirring speed is set to 1000r / min, and the reaction is carried out at a constant temperature within a temperature range of 55°C. The precipitant and complexing agent are added to adjust the pH in the reactor. The pH is kept constant during the reaction, and the pH is 9.5. After continuous reaction, the product is centrifuged, washed, filtered, and dried to obtain a nickel-cobalt-manganese hydroxide precursor with a volume distribution Dv50 of 11.2μm.

[0116] S2: The nickel cobalt manganese hydroxide precursor prepared in step S1 is mixed with LiOH·H2O and MoO3 powder with a molar ratio of 0.003 in a plow mixer, and subjected to a first sintering to obtain a first lithium nickel cobalt manganese oxide. The molar ratio of LiOH·H2O to the total transition metal in the nickel cobalt manganese hydroxide precursor is Li / Me, which is 1.03, Me is the total mole of Ni, Co, and Mn elements, the first sintering temperature is 710°C, the first sintering time is 15 hours, and the first sintering atmosphere is O2.

[0117] S3: The first lithium nickel cobalt manganese oxide obtained in step S2 is mixed with Co(OH)2 and sintered for a second time, wherein the amount of Co(OH)2 added is 15000ppm by mass of Co element based on the first lithium nickel cobalt manganese oxide, the second sintering temperature is 600°C, the second sintering time is 8h, and the second sintering atmosphere is air, to obtain a second lithium nickel cobalt manganese oxide, i.e., the surface of the first lithium nickel cobalt manganese oxide is coated with cobalt oxide.

[0118] S4: Mix the second lithium nickel cobalt manganese oxide obtained in step S3 with B2O3, and perform a third sintering to obtain a third lithium nickel cobalt manganese oxide, which is the target product. The third lithium nickel cobalt manganese oxide is the surface of the first lithium nickel cobalt manganese oxide coated with cobalt oxide and boron oxide. Among them, the amount of B2O3 added is that the mass of the B element accounts for 1000ppm of the second lithium nickel cobalt manganese oxide; the third sintering temperature is 350°C, the third sintering time is 6h, and the third sintering atmosphere is O2.

[0119] In the embodiment of the present application, the third lithium nickel cobalt manganese oxide is used as the positive electrode active material, Li 1.01 Ni 0.917 Co 0.07 Mn 0.01 Mo 0.003 O2, the surface is coated with cobalt oxide and boron oxide. Figure 4 , which is a scanning electron microscope image of a cross-section of the positive electrode active material of Embodiment 1. It can be seen from the image that the positive electrode active material of the present application includes secondary particles, and the secondary particles include primary particles.

[0120] Preparation method of positive electrode sheet:

[0121] The positive electrode active material, conductive carbon black (Super-P) and polyvinylidene fluoride (PVDF) were mixed with N, N-dimethylpyrrolidone (NMP) at a weight ratio of 96.5:3:1.5, and stirred evenly to obtain the slurry of the positive electrode sheet, and the slurry of the positive electrode sheet was evenly coated on both sides of the aluminum foil. The electrode sheet was cold pressed and sliced ​​to obtain the positive electrode sheet.

[0122] Preparation method of negative electrode sheet:

[0123] In the embodiment of the present application, the negative electrode active material, the conductive agent, the thickener and the binder are mixed with deionized water to form a slurry of the negative electrode sheet. Specifically, in the embodiment of the present application, the negative electrode active material includes a silicon-based material and a carbon-based material. The carbon-based material is artificial graphite, and the silicon-based material is nano-silicon. The conductive agent is conductive carbon black (Super-P) and carbon nanotubes. The thickener is sodium carboxymethyl cellulose (CMC-Na). The binder is styrene-butadiene rubber (SBR).

[0124] Specifically, in the embodiment of the present application, artificial graphite, conductive carbon black (Super-P), carbon nanotubes, sodium carboxymethyl cellulose (CMC-Na), and styrene-butadiene rubber (SBR) are mixed with deionized water in a weight ratio of 96.9:0.5:0.1:1:1.5, and stirred evenly to obtain a slurry for coating the negative electrode sheet. The viscosity can be adjusted by deionized water during the stirring process. Then, the slurry is coated on both sides of the negative electrode collector with a certain width, and the negative electrode sheet is obtained by cold pressing and slicing. In the embodiment of the present application, the negative electrode collector is a 6μm thick copper foil, and the embodiment of the present application does not limit the material and thickness of the negative electrode collector.

[0125] Preparation method of lithium ion secondary battery:

[0126] The positive electrode sheet, the separator and the negative electrode sheet are wound into a battery cell assembly, and a lithium-ion secondary battery is obtained by welding the pole ears, packaging the aluminum shell, injecting liquid, packaging and forming, and vacuum forming. The width of the battery cell assembly is 148mm, the thickness is 28mm, the height is 98mm, and the capacity is 60Ah. Among them, the injected electrolyte is a 1mol / L LiPF6 solution, and the solvent of the LiPF6 solution is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the volume ratio of ethylene carbonate (EC) and dimethyl carbonate (DMC) is 1:2. In the embodiment of the present application, the separator adopts 7μm thick polyethylene (PE).

[0127] The lithium-ion secondary battery obtained in the embodiment of the present application includes a positive electrode sheet and a negative electrode sheet, the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel in all transition metal elements is 0.918; the positive electrode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 400nm. The primary particles include radial primary particles, wherein, in the cross-sectional scanning electron microscope image of the secondary particles, the long axis direction of the primary particles is the direction of the line between the two farthest points on the surface of the primary particles, the radial direction of the secondary particles is the direction of the line between the nearest point of the long axis of the primary particles close to the center of the circle and the center of the circle, and the radial primary particles are primary particles whose minimum angle between the long axis direction of the primary particles and the radial direction of the secondary particles is less than or equal to 20°. The secondary particles include the first secondary particles, and in the cross-sectional scanning electron microscope image of the first secondary particles, the total area of ​​the radial primary particles accounts for 89% of the total area of ​​the cross section of the first secondary particles; the crushing force of the first secondary particles is 38mN.

[0128] Embodiment 2-7

[0129] The other differences from Example 1 are detailed in Table 1 and Table 2, and the rest are similar to Example 1.

[0130] Comparative Example 1

[0131] Preparation method of positive electrode active material:

[0132] S1: Prepare nickel-cobalt-manganese hydroxide drive body by coprecipitation reaction: According to the molar ratio of Ni, Co and Mn elements in the high nickel ternary material substrate of 0.917:

[0133] A sulfate solution of Ni, Co, and Mn with a concentration of 6 mol / L is prepared in a ratio of 0.07:0.01, and a 4 mol / L NaOH solution and a 3 mol / L ammonia solution are prepared at the same time. Pure water accounting for 30% by volume is added to the reactor, and the above three solutions are pumped into the reactor. The flow rate of sulfate and ammonia water is kept constant during the reaction. The stirring speed is set to 1000r / min, and the reaction is carried out at a constant temperature within a temperature range of 55°C. A precipitant and a complexing agent are added to adjust the pH in the reactor. The pH is kept constant during the reaction at 10.8. After continuous reaction, the product is centrifuged, washed, filtered, and dried to obtain a nickel-cobalt-manganese hydroxide precursor with a volume distribution Dv50 of 11μm.

[0134] S2: The nickel cobalt manganese hydroxide precursor prepared in step S1 is mixed with LiOH·H2O and MoO3 powder with a molar ratio of 0.003 in a plow mixer, and subjected to a first sintering to obtain a first lithium nickel cobalt manganese oxide. The molar ratio of LiOH·H2O to the total transition metal in the nickel cobalt manganese hydroxide precursor is Li / Me, which is 1.03, Me is the total mole of Ni, Co, and Mn elements, the first sintering temperature is 710°C, the first sintering time is 15 hours, and the first sintering atmosphere is O2.

[0135] S3: The first lithium nickel cobalt manganese oxide obtained in step S2 is mixed with Co(OH)2 and sintered for a second time, wherein the amount of Co(OH)2 added is 15000ppm by mass of Co element based on the first lithium nickel cobalt manganese oxide, the second sintering temperature is 600°C, the second sintering time is 8h, and the second sintering atmosphere is air, to obtain a second lithium nickel cobalt manganese oxide, i.e., the surface of the first lithium nickel cobalt manganese oxide is coated with cobalt oxide.

[0136] S4: Mix the second lithium nickel cobalt manganese oxide obtained in step S3 with B2O3, and perform a third sintering to obtain a third lithium nickel cobalt manganese oxide, which is the target product. The third lithium nickel cobalt manganese oxide is the surface of the first lithium nickel cobalt manganese oxide coated with cobalt oxide and boron oxide. Among them, the amount of B2O3 added is that the mass of element B accounts for 1000ppm of the second lithium nickel cobalt manganese oxide; the third sintering temperature is 350°C, the third sintering time is 6h, and the third sintering atmosphere is O2. In Comparative Example 1, the nickel cobalt manganese hydroxide precursor is a secondary particle, and the secondary particles include primary particles. The morphology distribution of the primary particles is disordered, and the primary particles in the secondary particles of the formed positive electrode active material are distributed more disorderly, and the content of radial primary particles is low.

[0137] The lithium ion secondary batteries of Examples 1-7 and Comparative Example 1 were subjected to battery performance tests. The positive electrode active materials were subjected to standard tests.

[0138] 1) A test on the area ratio of the total area of ​​radial primary particles to the total area of ​​the cross section of the first type of secondary particles.

[0139] The secondary particles of the positive electrode active material were tested by ion milling scanning electron microscopy (CP-EDS), and cross-sectional scanning electron microscope images of secondary particles with a particle size of 6 to 15 μm were taken, for a total of 50. For each primary particle in the secondary particle, the radial condition of the primary particle was determined using the two farthest points, and the primary particles that met the radial requirements were calibrated using Image software. The software was used to count the areas of all primary particles that met the radial requirements, and the radial primary particle area was compared with the cross-sectional area of ​​the secondary particles to obtain the area ratio. All 50 secondary particles were counted to obtain the average area ratio.

[0140] 2) Crushing force test of secondary particles.

[0141] The single particle (secondary particle) crushing force test equipment mainly includes a pressure measurement system, a displacement measurement system and a force-displacement control system. After the equipment pressure head acts directly on a single particle, the stress-strain curve after the action is collected through high-precision displacement and pressure control, and the single particle crushing force is obtained from the mutation point of the curve.

[0142] 3) Test on the quantity ratio of the first type of secondary particles in the secondary particles.

[0143] 50 secondary particles are randomly counted, and an area ratio test of the total area of ​​radial primary particles to the total area of ​​the cross-section of the first secondary particles and a Young's modulus test are performed on them. The number of the first secondary particles is counted, and the number of the first secondary particles is compared with 50 to obtain a test on the ratio of the number of the first secondary particles in the secondary particles.

[0144] 4) The average particle size of a particle.

[0145] The positive electrode active material was tested using a ZEISS sigma 300 scanning electron microscope, and then tested according to the standard JY / T010-1996 to observe the sample morphology.

[0146] Software name: LIBMAS Lithium-ion Battery Material Microscopic Intelligent Analysis System. The scanning electron microscope image of the positive electrode active material is used to automatically identify the single crystal particles by LIBMAS Lithium-ion Battery Material Microscopic Intelligent Analysis System. The particle outline, particle quantity, number, area, maximum caliper diameter, average number, and manual intervention can be drawn. The average particle size of the primary particle = the sum of all measured particle sizes / the sum of all measured primary particle numbers.

[0147] 5) Measurement of the major axis length of the primary particle.

[0148] The secondary particles of the positive electrode active material were subjected to ion milling scanning electron microscopy (CP-EDS) testing, cross-sectional scanning electron microscopy images of secondary particles with a particle size of 6 to 15 μm were taken, and the major axis lengths of 50 primary particles were measured.

[0149] 6) Specific surface area test of positive electrode active material.

[0150] The sample to be tested is prepared into a uniform powder or granular form, then placed in a vacuum and set to a specific treatment temperature to remove the gas and moisture adsorbed on the surface. The sample is placed in an adsorption instrument, the liquid nitrogen temperature is set to 77.35K, and the adsorption isotherm is measured by gradually increasing the nitrogen pressure. According to the adsorption isotherm data, the BET equation is used for fitting to obtain the slope and intercept of the adsorption isotherm. According to the parameters in the BET equation, the specific surface area of ​​the sample is calculated.

[0151] 7) Testing of cross-section porosity and cross-section average pore size of positive electrode active materials.

[0152] Test method: Use PVDF to adhere the sample powder to aluminum foil, place it under an argon ion beam thinner for cutting, place the cut section under a scanning electron microscope for observation, take a SEM image of the material cross-section, use imageJ graphics software to identify the pore part and calculate the area, and then use the ratio of the pore area to the total area to calculate the porosity.

[0153] The pore size is directly measured using the SEM image. 50 pore sizes are measured and the average value is calculated to obtain the average pore size of the cross section.

[0154] 8) Volume average particle size DV2, DV50 test

[0155] Equipment model: Malvern 2000 (MasterSizer 2000) laser particle size analyzer, reference standard process: GB / T19077-2016 / ISO 13320:2009, specific test process: take an appropriate amount of the sample to be tested (the sample concentration is guaranteed to be 8%-12% shading), add 20mL of deionized water, and simultaneously ultraviolet for 5min (53KHz / 120W) to ensure that the sample is completely dispersed, and then measure the sample according to GB / T19077-2016 / ISO 13320:2009 standard.

[0156] 9) Test on the change rate of volume average particle size Dv2 of positive electrode active material.

[0157] The volume average particle size Dv2 of the tested positive electrode material is X1.

[0158] 1g of positive electrode active material powder was placed in a powder compacting mold and pressed with a pressure of 5T for 15min. The pressed powder was then taken out and tested with a laser particle size analyzer. The volume average particle size Dv2 was measured to be X2. The volume average particle size Dv2 of the positive electrode active material changed by

[0159]

[0160] 10) Lithium-ion secondary battery cycle capacity retention rate test.

[0161] The specific test conditions are: at 25°C, 1 / 3C standard (nominal capacity) constant current charging to a termination voltage of 4.4V, and then constant voltage charging to 0.05C 标 , leave for 5 minutes, then heat to 1 / 3C 标 Discharge to the discharge cut-off voltage of 2.5V, and obtain the discharge energy E and capacity C, which is recorded as the initial capacity C0. Repeat the above steps for the same lithium-ion secondary battery, and record the discharge capacity Cn of the battery after the nth cycle at the same time, then the battery capacity retention rate after each cycle Pn = Cn / C0 × 100%. In this test process, the first cycle corresponds to n = 1, the second cycle corresponds to n = 2, ... the 100th cycle corresponds to n = 100, and the capacity retention rate after 100 cycles is tested.

[0162]

[0163]

[0164] From Table 1, Table 2 and Figure 4It can be seen that in Examples 1 to 7 of the present application, the molar content of nickel in the obtained lithium nickel cobalt manganese oxide in the total transition metal oxide is greater than or equal to 0.85, the positive electrode active material includes secondary particles, the secondary particles include primary particles, the total area of ​​the radial primary particles accounts for 60% to 95% of the total area of ​​the cross section of the first secondary particles; the crushing force of the first secondary particles is 2mN to 48mN. The total area of ​​the cross section of the first secondary particles in Comparative Example 1 accounts for 30%, and the crushing force of the first secondary particles is 1.8mN. The total area of ​​the radial primary particles in the embodiment of the present application accounts for a significantly increased proportion of the total area of ​​the cross-section of the first secondary particles. The first secondary particles have a larger crushing force, so that the capacity retention rate of the positive electrode active material after 100 cycles is 93.7% to 97.1%, which is significantly increased relative to comparative example 1. This indicates that more and larger primary particles inside the first secondary particles are oriented toward the center of the first secondary particles, and the primary particles are more ordered, which can reduce the probability of cracking of the secondary particles and improve the chemical cycle performance of lithium-ion secondary batteries.

[0165] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A lithium ion secondary battery, characterized in that: Including positive electrode sheet, negative electrode sheet and electrolyte, The positive electrode plate includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel element in all transition metal elements is greater than or equal to 0.85 and less than 1; The positive electrode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 50nm to 2μm; The primary particles include radial primary particles, wherein, in the cross-sectional scanning electron microscope image of the secondary particles, the long axis direction of the primary particles is the direction of the line between the two farthest points on the surface of the primary particles, the radius direction of the secondary particles is the direction of the line between the nearest point of the long axis of the primary particles close to the center of the circle and the center of the circle, and the radial primary particles are primary particles whose minimum angle between the long axis direction of the primary particles and the radius direction of the secondary particles is less than or equal to 20°; The secondary particles include first secondary particles. In the cross-sectional scanning electron microscope image of the first secondary particles, the total area of ​​the radial primary particles accounts for 60% to 95% of the total area of ​​the cross-section of the first secondary particles; the crushing force of the first secondary particles is 2mN to 50mN.

2. The lithium-ion secondary battery according to claim 1, characterized in that: In the scanning electron microscope image of the cross section of the first secondary particle, the total area of ​​the radial primary particles accounts for 70% to 90% of the total area of ​​the cross section of the first secondary particle; and / or, The crushing force of the first secondary particles is 10 mN to 40 mN; and / or, The average particle size of the primary particles is 100 nm to 500 nm.

3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The volume average particle size DV2 of the positive electrode active material is 0.5 μm to 4 μm; and / or, The volume average particle size Dv50 of the positive electrode active material is 9 μm to 12 μm, and / or the major axis length of the primary particles is 0.3 μm to 3 μm; and / or, The cross-sectional porosity of the positive electrode active material is 2% to 8%, and / or The cross-sectional average pore size of the positive electrode active material ranges from 0.1 μm to 2 μm, and / or, The first type of secondary particles accounts for 80% to 100% of the secondary particles.

4. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: The volume average particle size DV2 of the positive electrode active material is 0.8 μm to 3 μm; and / or, In the cross-sectional scanning electron microscope image of the secondary particle, the major axis length of the primary particle is 0.5 μm to 2 μm; and / or, The cross-sectional porosity of the positive electrode active material is 3% to 6%; and / or, The amount of the first type of secondary particles in the secondary particles accounts for 90% to 100%.

5. The lithium ion secondary battery according to any one of claims 1 to 4, characterized in that: The positive electrode active material has a range of 0 to 4.9×10 4 N, the change rate of the volume average particle size Dv2 of the positive electrode active material is less than or equal to 20%.

6. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The nickel content of the first secondary particles from the center to the surface area is equal, or the difference in the nickel content from the center to the surface area is less than or equal to 2%; The manganese content of the first secondary particles from the center to the surface area is equal, or the difference in the manganese content from the center to the surface area is less than or equal to 0.5%.

7. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 e O f material, wherein the M1 element is one or more combinations of Zr, Ti, Y, Sb, W, Mo, Ba, Ta, Nb, Al, etc., 0.9≤a≤1.2, 0.85≤b<1, 0.01≤c≤0.09, 0.01≤d≤0.05, 0.001≤e≤0.005, 1.8≤f≤2.2, b+c+d+e=1.

8. The lithium-ion secondary battery according to claim 7, characterized in that: The structural formula is Li a Ni b Co c Mn d M1 e O f The surface of the material also includes a coating layer, and the coating layer includes Co and / or B elements.

9. A positive electrode active material, characterized in that: The positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar content of nickel in all transition metal elements is greater than or equal to 0.85 and less than 1; The positive electrode active material includes secondary particles, the secondary particles include primary particles, and the average particle size of the primary particles is 50nm to 2μm; The primary particles include radial primary particles, wherein, in the cross-sectional scanning electron microscope image of the secondary particles, the long axis direction of the primary particles is the direction of the line between the two farthest points on the surface of the primary particles, the radius direction of the secondary particles is the direction of the line between the nearest point of the long axis of the primary particles close to the center of the circle and the center of the circle, and the radial primary particles are primary particles whose minimum angle between the long axis direction of the primary particles and the radius direction of the secondary particles is less than or equal to 20°; The secondary particles include first secondary particles. In the cross-sectional scanning electron microscope image of the first secondary particles, the total area of ​​the radial primary particles accounts for 60% to 95% of the total area of ​​the cross-section of the first secondary particles; the crushing force of the first secondary particles is 2mN to 50mN.

10. An electrical device, characterized in that: The invention comprises the lithium ion secondary battery according to any one of claims 1 to 8 and / or the positive electrode active material according to claim 9.

Citation Information

Patent Citations

  • Positive electrode material for lithium ion battery with nonaqueous electrolyte, and battery using the same

    CN101167209A

  • Pressure-resistant positive electrode active material and electrochemical energy storage device

    CN111384371A

  • Positive electrode active material and secondary battery

    CN117691068A

Cited By

  • Positive electrode material, positive plate and battery

    CN121172123A